2010
DOI: 10.1007/s00114-010-0674-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance island hopping without dispersal stages: transportation across major zoogeographic barriers in a Southern Ocean isopod

Abstract: Species integrity is maintained only if recurrent allelic exchange between subpopulations occurs by means of migrating specimens. Predictions of this gene flow on the basis of observed or assumed mobility of marine species have proven to be error-prone. Using one mitochondrial gene and seven microsatellite markers, we studied the genetic structure and gene flow in Septemserolis septemcarinata, a strictly benthic species lacking pelagic larvae and the ability to swim. Suitable shallow-water habitats around thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 59 publications
2
67
0
Order By: Relevance
“…Also, the radiation of the many Antarctic P. patagonica species very likely started in the late Pliocene and increased during the Pleistocene (last 2.5 myr). Such patterns have been reported before (e.g., Held, 2000;Page and Linse, 2002;Thornhill et al, 2008;Krabbe et al, 2010;Leese et al, 2010;Hemery et al, 2012;Dietz et al, 2015a,b) suggesting that over evolutionary time scales the Polar Front has not been an impermeable barrier to gene flow in general, though we did not observe across Drake Passage exchange in more recent clades of P. patagonica s.l. However, in view of the above-mentioned limitations of molecular clock calculations, we advise to use the divergence estimates made here with caution.…”
Section: Divergence Datessupporting
confidence: 83%
“…Also, the radiation of the many Antarctic P. patagonica species very likely started in the late Pliocene and increased during the Pleistocene (last 2.5 myr). Such patterns have been reported before (e.g., Held, 2000;Page and Linse, 2002;Thornhill et al, 2008;Krabbe et al, 2010;Leese et al, 2010;Hemery et al, 2012;Dietz et al, 2015a,b) suggesting that over evolutionary time scales the Polar Front has not been an impermeable barrier to gene flow in general, though we did not observe across Drake Passage exchange in more recent clades of P. patagonica s.l. However, in view of the above-mentioned limitations of molecular clock calculations, we advise to use the divergence estimates made here with caution.…”
Section: Divergence Datessupporting
confidence: 83%
“…This is demonstrated by a number of molecular studies that have simply confirmed morphological data (e.g. Westheide and Schmidt 2003, Leese et al 2010, Nikula et al 2010, Brix et al 2011, Gollner et al 2011, Kieneke et al 2012, Brix et al 2014, including species with wide geographic distributions. Jörger et al (2014) has in fact found that molecular approaches are not always able to address all uncertainties regarding species delineation.…”
Section: Key To Species Of Paralaophontodes (Females)mentioning
confidence: 82%
“…A potential explanation for the maintenance of genetic connectivity in brooding species or those lacking pelagic larvae includes the passive rafting of larvae or adults on floating substrate or ocean debris (Waters, 2008). Leese et al (2010) suggested that this method maintained connected shallow water isolated populations of the isopod Septemserolis septemcarinata across the sub-Antarctic. Furthermore, direct evidence of rafting on kelp has been observed in the widespread sub-Antarctic brooding bivalve Gasimardia trapesina (Helmuth et al, 1994), the sea slug Onchidella marginata (Cumming et al, 2014) and two species of sub-Antarctic amphipods (Nikula et al, 2010).…”
Section: The Use Of Particle Tracking Analysis To Understand Antarctimentioning
confidence: 99%